Why do we follow sporting events? - Pori, Maja (Array, 2009)
Abstract: The aim of the study was to investigate the motives for following sporting events and their dependence upon gender and age of spectators. The study was based on a survey of 1727 adult Slovenes. According to the results the most important motives could be classified in the category of Dionysian values. This means that the role of sport in a spectator's life is not that influential; it is much more considered a source of relaxation and pleasure. Higher values of all motives were given by men. Women found the motive »National importance of sport« more important, while the motives »Attraction of sports« and »Competitiveness, fighting spirit, victory« were placed higher by men. Younger spectators evaluated the motives higher, with motives »Pleasure, Entertainment« and »Sport Dynamism« being most important. The data reveal those attributes of sport that have always caught and will also continue to catch the eye of the spectators